The Role of Fiscal Policy in Economic Growth in Indonesia - Saragih, Wike Ardinawati; Tanjung, Ahmad Albar; Syafii, M. (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the influence of economic variables on Indonesia's economic growth in the short and long term. In this analysis, four main economic variables are evaluated: Goods Expenditures, Taxes, Subsidies, and Human Capital. The research results show that goods spending has a positive but not significant influence on economic growth, both in the short and long term. Meanwhile, taxes show a positive and significant influence on economic growth in both periods. However, subsidies are proven to have a negative and significant effect, indicating that providing subsidies may affect economic growth negatively in the short and long term. Apart from that, Human Capital also shows a negative and significant influence, highlighting the importance of investment in human resources to support sustainable economic growth in Indonesia. These findings provide valuable insights for economic policy that can be used to design more effective strategies for increasing Indonesia's economic growth.